MHC-E-restricted CD8+ T cells target Hepatitis B virus-infected human hepatocytes - Burwitz, Benjamin J. (J Immunol, 2020)
Currently 247 million people are living with chronic HBV infection (CHB), and the development of novel curative treatments is urgently needed. Immunotherapy is an attractive approach to treat CHB, yet therapeutic approaches to augment the endogenous HBV-specific T cell response in CHB patients have demonstrated little success. Here, we show that strain 68–1 rhesus cytomegalovirus vaccine vectors expressing HBV antigens (RhCMV/HBV) engender HBV-specific CD8+ T cells unconventionally restricted by major histocompatibility complex (MHC) class II and the non-classical MHC-E molecule in rhesus macaques (RM). Surface staining of human donor (HD) and RM primary hepatocytes (PH) ex vivo revealed the majority of PH expressed MHC-E, but not MHC-II. HBV-specific, MHC-E-restricted CD8+ T cells from RhCMV/HBV-vaccinated RM recognized HBV-infected PH from both HD and RM. These results provide proof-of-concept that MHC-E-restricted CD8+ T cells could be harnessed for the treatment of CHB, either through therapeutic vaccination or adoptive immunotherapy.